2007
DOI: 10.1128/jvi.00746-07
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Integration of Adeno-Associated Virus Type 2 into a Polypyrimidine/Polypurine-Rich Region within AAVS1

Abstract: Adeno-associated virus type 2 (AAV2) preferentially integrates its genome into the AAVS1 locus on human chromosome 19. Preferential integration requires the AAV2 Rep68 or Rep78 protein (Rep68/78), a Rep68/78 binding site (RBS), and a nicking site within AAVS1 and may also require an RBS within the virus genome. To obtain further information that might help to elucidate the mechanism and preferred substrate configurations of preferential integration, we amplified junctions between AAV2 DNA and AAVS1 from AAV2-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…1). Few of the previously identified left junctions were found closer to the TRS/RBS motifs (22,24,25), suggesting that the left cellular breakpoint might occur anywhere downstream of the TRS motif, most frequently at a considerable distance. In a recent study, Drew et al (26) identified 11 left viral-cellular junctions, of which the cellular breakpoints were scattered from 2.3 kb to Ͼ14 kb from the TRS motif (26).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1). Few of the previously identified left junctions were found closer to the TRS/RBS motifs (22,24,25), suggesting that the left cellular breakpoint might occur anywhere downstream of the TRS motif, most frequently at a considerable distance. In a recent study, Drew et al (26) identified 11 left viral-cellular junctions, of which the cellular breakpoints were scattered from 2.3 kb to Ͼ14 kb from the TRS motif (26).…”
Section: Discussionmentioning
confidence: 96%
“…Other hallmarks are the microhomology between the viral and cellular sequences, the presence of a short ''unknown'' sequence (23,24), and the close proximity of the right junction to the cellular TRS motif. It should be noted that most previous studies focused on the isolation of viral-cellular junctions based on direct PCR technologies that would only allow for the amplification of junctions located close to the AAVS1 TRS/RBS motifs (17,24).…”
Section: Discussionmentioning
confidence: 99%
“…They are defective viruses that require coinfection with adenovirus for productive infection 12,13 . Early studies showed that, during infection, the AAV2 DNA integrates into the human genome, where it remains quiescent until a new parvovirus infection occurs 12,14,15 . To investigate the functional consequences of viral integration, we generated a construct based on the pGL3 reporter vector, reproducing the exact AAV2 inserted sequence.…”
mentioning
confidence: 99%
“…Interestingly, the analysis of the AAVS1-AAV junctions also revealed that many integration junctions corresponded to short regions of homology between AAV and AAVS1 sequences (65,67,68). These findings strongly suggest that AAV integration might be the result of a DNA repair pathway involving end-joining via microhomologies.…”
Section: Discussionmentioning
confidence: 75%